(untitled) (Boletín de Investigaciones Marinas y Costeras, 2016)
Between 1998 and 2001 the INVEMAR-MACROFAUNA cruises collected a series of deep water samples between the Guajira Peninsula and off the Gulf of Urabá, ranging in depths from 270 to about 520 m. Among the material collected a single chiton species Leptochiton binghami was recognized. The new locality record extends the known distributional range of the species to Colombian waters.